DIXDC1 Phosphorylation and Control of Dendritic Morphology Are Impaired by Rare Genetic Variants - Vickie Kwan; Durga Praveen Meka; Sean H. White; Claudia L. Hung; Nicholas T. Holzapfel; Susan Walker; Nadeem Murtaza; Brianna K. Unda; Birgit Schwanke; Ryan K.C. Yuen; Kendra Habing; Chloe Milsom; et al. (Cell Reports, 2016)
The development of neural connectivity is essential for brain function, and disruption of this process is associated with autism spectrum disorders (ASDs). DIX domain containing 1 (DIXDC1) has previously been implicated in neurodevelopmental disorders, but its role in postnatal brain function remains unknown. Using a knockout mouse model, we determined that DIXDC1 is a regulator of excitatory neuron dendrite development and synapse function in the cortex. We discovered that MARK1, previously linked to ASDs, phosphorylates DIXDC1 to regulate dendrite and spine development through modulation of the cytoskeletal network in an isoform-specific manner. Finally, rare missense variants in DIXDC1 were identified in ASD patient cohorts via genetic sequencing. Interestingly, the variants inhibit DIXDC1 isoform 1 phosphorylation, causing impairment to dendrite and spine growth. These data reveal that DIXDC1 is a regulator of cortical dendrite and synaptic development and provide mechanistic insight into morphological defects associated with neurodevelopmental disorders.